2013
DOI: 10.2807/1560-7917.es2013.18.38.20586
|View full text |Cite
|
Sign up to set email alerts
|

Insidious reintroduction of wild poliovirus into Israel, 2013

Abstract: Israel was certified as polio-free country in June 2002, along with the rest of the World Health Organization European Region. Some 11 years later, wild-type polio virus 1 (WPV1) was isolated initially from routine sewage samples collected between 7 and 13 April 2013 in two cities in the Southern district. WPV1-specific analysis of samples indicated WPV1 introduction into that area in early February 2013. National supplementary immunisation with oral polio vaccine has been ongoing since August 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 12 publications
3
122
0
2
Order By: Relevance
“…The investigation and response [13] included highly intensified environmental surveillance, first in other communities in southern Israel and subsequently nationwide. The sampling strategy included mostly sample collection at STFs but on several occasions, particularly when STFs represented separate communities, additional samples were collected from upstream sewage lines by a mobile laboratory operated by the Central Virology Laboratory using portable samplers.…”
Section: Detection Of Soas-wpv1 Importation To Southern Israel and Inmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigation and response [13] included highly intensified environmental surveillance, first in other communities in southern Israel and subsequently nationwide. The sampling strategy included mostly sample collection at STFs but on several occasions, particularly when STFs represented separate communities, additional samples were collected from upstream sewage lines by a mobile laboratory operated by the Central Virology Laboratory using portable samplers.…”
Section: Detection Of Soas-wpv1 Importation To Southern Israel and Inmentioning
confidence: 99%
“…Identification of the plaques as WPV1 suggested an importation and possible circulation of WPV1 in the region [13]. These alarming findings prompted an urgent assessment and response by the Public Health Services of the Ministry of Health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The editorial was responding to California's firstin-the-nation broad medical-marijuana law and DEA agents' subsequent threats to revoke the DEA registrations of California physicians who suggested that a patient might benefit from marijuana as permitted by the new law. 2 California has now been joined by more than 20 additional states in permitting patients to possess marijuana on the advice of their physician (see table).…”
Section: Lessons From a Publicmentioning
confidence: 99%
“…The first one concerned the sustainability and interpretation of our supplementary environmental surveillance. Since the last poliomyelitis outbreak in Israel in 1988, 1 the country has developed the capacity in our environmental laboratories to detect pathogens such as polioviruses in very low quantities within large volumes of sewage, and we have fully deployed this high-sensitivity detection on a national scale. This system routinely covered approximately 30 to 40% of the population in a representative fashion, 2 and it was substantially intensified beginning in June 2013, shortly after the detection of the wild poliovirus importation.…”
mentioning
confidence: 99%